2005
DOI: 10.1007/s11130-005-6837-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bitter Gourd (Momordica charantia) on Glycaemic Status in Streptozotocin Induced Diabetic Rats

Abstract: Abstract. Bitter gourd (Momordica charantia), a commonly consumed vegetable is used as an adjunct in the management of diabetes mellitus. A study was carried out to examine the effect of edible portion of bitter gourd at 10% level in the diet in streptozotocin induced diabetic rats. To evaluate the glycaemic control of bitter gourd during diabetes, diet intake, gain in body weight, water intake, urine sugar, urine volume, glomerular filtration rate and fasting blood glucose profiles were monitored. Water consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 23 publications
2
40
0
3
Order By: Relevance
“…From the present study it was found that after administration of Karela fruit powder for 60 days, the percentage of plasma glucose level declined statistically significant by 7.4% in normal subjects and by 7.53% in diabetic subjects. Our results were similar to studies conducted by [12][13][14][15] on streptozotocin diabetic animals. Khanna P, Jain SC et.…”
Section: Discussionsupporting
confidence: 92%
“…From the present study it was found that after administration of Karela fruit powder for 60 days, the percentage of plasma glucose level declined statistically significant by 7.4% in normal subjects and by 7.53% in diabetic subjects. Our results were similar to studies conducted by [12][13][14][15] on streptozotocin diabetic animals. Khanna P, Jain SC et.…”
Section: Discussionsupporting
confidence: 92%
“…Since M. charantia and its various extracts and components have been reported to exert hypoglycemic effects, and then it is important to understand whether M. charantia may have a direct effect in inducing a reduction in blood glucose level [62] . Previous studies have shown that both the aqueous and alcoholic extracts of the fruit of M. charantia can inhibit the activities of fructose 1, 6-diphosphatase and glucose-6-phosphatase and at the same time stimulating the action of glucose-6-phosphatase dehydrogenase [85] . It was previously reported that M. charantia and its various extracts can stimulate peripheral cell glucose uptake [71,72] .…”
Section: Charantia and Glucose Metabolismmentioning
confidence: 97%
“…It increases sensitivity of the insulin receptor [17], reduces insulin resistance and hyperinsulinemia, with favourably influence on the metabolic syndrome [18] and diabetes [19] in humans. Obesity promotes prostate cancer [20] which has been related to hyperinsulinemia and insulin resistance [2,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%